How to easily detect plant NADH-glutamate dehydrogenase (GDH) activity? A simple and reliable in planta procedure suitable for tissues, extracts and heterologous microbial systems. (March 2021) - Marchi, L.; Degola, F.; Baruffini, E.; Restivo, F.M.
Highlights: Simple and high throughput procedures to determine glutamate dehydrogenase (GDH) activity are desirable but still lacking. An in planta GDH enzymatic activity detection was developed and validated. The simple colorimetric method for GDH assay proved to be reliable for both plant tissues/organs and protein extracts. Abstract: Plant NADH glutamate dehydrogenase (GDH) is an intriguing enzyme, since it is involved in different metabolic processes owing to its reversible (anabolic/catabolic) activity and due to the oligomeric nature of the enzyme, that gives rise to several isoforms. The complexity of GDH isoenzymes pattern and the variability of the spatial and temporal localization of the different isoforms have limited our comprehension of the physiological role of GDH in plants. Genetics, immunological, and biochemical approaches have been used until now in order to shed light on the regulatory mechanism that control GDH expression in different plant systems and environmental conditions. We describe here the validation of a simple in planta GDH activity staining procedure, providing evidence that it might be used, with different purposes, to determine GDH expression in plant organs, tissues, extracts and also heterologous systems.